2013
DOI: 10.2106/jbjs.l.00589
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Surgical Decompression in Patients with Cervical Spondylotic Myelopathy

Abstract: Surgical decompression for the treatment of cervical spondylotic myelopathy was associated with improvement in functional, disability-related, and quality-of-life outcomes at one year of follow-up for all disease severity categories. Furthermore, complication rates observed in the study were commensurate with those in previously reported cervical spondylotic myelopathy series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
311
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 415 publications
(330 citation statements)
references
References 25 publications
(20 reference statements)
12
311
2
5
Order By: Relevance
“…8 In our study, 610 patients (88.79%) either stayed the same or improved, while 77 patients (11.21%) deteriorated based on mJOA scale scores. The MCID is a metric that describes a change in status that a patient would define as meaningful.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…8 In our study, 610 patients (88.79%) either stayed the same or improved, while 77 patients (11.21%) deteriorated based on mJOA scale scores. The MCID is a metric that describes a change in status that a patient would define as meaningful.…”
Section: Discussionmentioning
confidence: 47%
“…5,8 In general, surgical decompression of the cervical spine is effective at halting neurological deterioration, relieving certain symptoms, and improving functional status and quality of life. The minimum clinically important difference (MCID) is defined as the minimum change in a measurement that a patient would identify as beneficial.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the posterior and anterior approaches varied in the literature. Fehlings et al presented the results of 278 patients in the AO Spine North America prospective multicenter study and showed that anterior surgery was predominant in patients with mild (76.5%), moderate (61.8%), and severe (43.5%) conditions, ; however, it became inferior to posterior surgery (45.8%) in patients with severe CSM 9) . A Chinese study found posterior (76) and combined (58) surgeries were more common than anterior (19) surgery for 153 consecutive patients with multilevel CSM 10) .…”
Section: Discussionmentioning
confidence: 99%
“…Radiculopathy including C5 palsy, wound infection, hardware failure, and hematoma occurred following posterior surgeries 10,[20][21][22] . There were few reports that described general complications in CSM surgeries 9,19,23) , and there has not been a report that described the associations between general complications and surgical variables and preoperative conditions, including comorbidities.…”
Section: Discussionmentioning
confidence: 99%